Costs and Barriers Associated With the Recruitment of Children for a Nutrition Randomized Clinical Trial During COVID-19. (14th June 2022) - Leone, Julia; Clayton, Priscilla; Macchi, Alison; Galvan, Rodolfo; Ramirez, Daniela; Romero, Jorge; Dinou, Venus; Trak-Fellermeier, Maria; Palacios, Cristina
Abstract: Objectives: Recruitment of children for randomized clinical trials (RCT) is challenging, especially during a pandemic. This analysis aimed to (1) evaluate the cost and effectiveness of different recruitment strategies; (2) evaluate the reasons for exclusion; and (3) evaluate the barriers of participation. Methods: This is an analysis of the costs associated with recruitment in the MetA-Bone trial, an RCT testing the effects of soluble corn fiber supplementation on bone in children 10–13 y. Recruitment methods were categorized as (1) community-based (CB): healthcare providers, schools, companies/organizations, university, mailings, and word of mouth; (2) Online: email campaigns, social media; and (3) not specified. Totals of the cost and effectiveness of each recruitment method, participants' reasons for exclusions, and barriers to participation were calculated. Results: Preliminary results show the total number of screened participants was 238 from February 2020–2022. Email campaigns rendered the greatest number of pre-screened participants (n = 145), followed by mailings to home (n = 20). The total cost of recruitment was $92, 433 (CB = $74, 170 and online = $18, 264) with the highest cost being recruitment from healthcare providers ($40, 180) and the lowest cost being word of mouth ($80). The most cost-effective recruitment methods were word of mouth ($5 cost per participant) and email campaigns ($85 cost per participant). The reason for most participants being excluded from participating in the study was an incomplete pre-screening form (n = 91) or a BMI > 95 th percentile (n = 24). The reason for most eligible participants deciding not to enroll in the study was not specified (n = 9) or due to time commitment (n = 4). Conclusions: Online recruitment methods are more effective in recruiting children into a clinical trial during the pandemic based on the number of participants screened and low implementation costs. Specifically, email campaigns and word of mouth are the most effective recruitment methods associated with low cost per pre-screened participant. Funding Sources: The MetA-Bone trial is supported by the National Institutes of Health (Eunice Kennedy Shriver National Institute of Child Health and Human Development, NICHD), grant number 1R01HD098589–01. The funding source had no involvement in the preparation of the article or the study design.